About oxide dispersion particles chemical compatibility with areas coherent dissipation/sub-grains of bcc-alloys in Fe - (Cr, V, Mo, W) systems - Udovsky A.; Fabrichnaya O. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A concept of partial magnetic moments (PMM) of the iron atoms located in the first ч four coordination spheres (1÷4 CS) for bcc lattice have been introduced based on analysis of results obtained by quantum-mechanical calculations (QMC) for volume dependence of the average magnetic moment ferromagnetic (FM) Fe. The values of these moments have been calculated for pure bcc Fe and bcc - Fe-Cr alloys. This concept has been used to formulate a three sub-lattice model for binary FM alloys of the Fe-M systems (M is an alloying paramagnetic element). Physical reason for sign change dependence of the short-range order and mixing enthalpy obtained by QMCs for Fe-(Cr, V) bcc phases has been found. Using this model it has been predicted that static displacements of Fe - atoms in alloy matrix increase with increasing the of CS number and result in reducing of the area of coherent dissipation (ACD) size with growth of the dimension factor (DF) in the Fe-(Cr, V, Mo, W) systems in agreement with the X-ray experiments. It has been shown theoretically that anisotropy of spin- density in bcc lattice Fe and DF in binary Fe - (Cr, V, Mo, W) systems is main factor for origins of segregations on small angle boundaries of ACD and sub-grains boundaries To prevent the coagulation of both ACD and sub-grains, and to increase the strength of alloys, it is advisable to add oxide dispersion particles into ferrite steel taking into account their chemical compatibility and coherent interfacing with the crystalline lattice of a ferrite matrix. Application of phase diagrams for binary and ternary the Fe-(Y, Zr)-O systems to verify chemical compatibility of oxide dispersion particles with ferrite matrix have been discussed